2020
DOI: 10.1016/j.kint.2020.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Genetic testing for kidney disease of unknown etiology

Abstract: In many cases of chronic kidney disease, the cause of disease remains unknown despite a thorough nephrologic workup. Genetic testing has revolutionized many areas of medicine and promises to empower diagnosis and targeted management of such cases of kidney disease of unknown etiology. Recent studies using genetic testing have demonstrated that Mendelian etiologies account for approximately 20% of cases of kidney disease of unknown etiology. Although genetic testing has significant benefits, including tailoring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 101 publications
(137 reference statements)
0
53
0
Order By: Relevance
“…This idea has been supported by several recent studies that demonstrated significant diagnostic capabilities of genetic testing in patients with a variety of chronic kidney diseases. For example, genetic testing was shown to provide an accurate diagnosis in up to 40% of patients with kidney disease of unknown etiology [38]. Separately, recent gene sequencing studies have consistently demonstrated that variants in COL4A3 , COL4A4 , and COL4A5 commonly result in sporadic and familial adult FSGS, which should be identified as Alport syndrome based on the reclassification proposal [39, 40].…”
Section: Discussionmentioning
confidence: 99%
“…This idea has been supported by several recent studies that demonstrated significant diagnostic capabilities of genetic testing in patients with a variety of chronic kidney diseases. For example, genetic testing was shown to provide an accurate diagnosis in up to 40% of patients with kidney disease of unknown etiology [38]. Separately, recent gene sequencing studies have consistently demonstrated that variants in COL4A3 , COL4A4 , and COL4A5 commonly result in sporadic and familial adult FSGS, which should be identified as Alport syndrome based on the reclassification proposal [39, 40].…”
Section: Discussionmentioning
confidence: 99%
“…Karyotyping directly visualizes the entire set of 46 chromosomes during prometaphase or metaphase with a high sensitivity for aneuploidies, large deletions and duplications, and translocations. CMA is more sensitive for the detection of microdeletions or microduplications that are over 20-400 kilobases (Kb) in size, but cannot detect balanced translocations or inversions [13][14][15] . CMA in combination with karyotype is the test of choice when a structural variant is clinically suspected, as in developmental delay and multiple congenital anomalies.…”
Section: Diagnostic Genetic Testing and Diagnostic Yieldmentioning
confidence: 99%
“…1. Approach to genetic testing in children with kidney disease, which is modified from the suggested algorithm for kidney disease of unknown etiology by Hay et al 15) . CAKUT, congenital anomalies of the kidney and urinary tract; CMA, chromosomal microarray; SNRS, steroid-resistant nephrotic syndrome; VUS, variants of unknown significance; WES, whole exome sequencing.…”
Section: Diagnostic Approach and Interpretation Of Genetic Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…Knowledge of the underlying kidney disease is crucial for ESRD management in the context of transplantation, as the primary etiology may affect graft survival in terms of recurrence and or rejection 7 10 . Moreover, a genetic diagnosis may be of pivotal importance for family counseling and in the setting of kidney transplantation, particularly when living related donation is involved 9 , 11 .…”
Section: Introductionmentioning
confidence: 99%